The age of migration international population movements in the modern world - Castles, Stephen; Haas, Hein de 1969-; Miller, Mark J. (Guilford Press, 2014)
"The leading text in the field, this authoritative work offers a global perspective on the nature of migration flows, why they occur, and their consequences for both origin and destination societies. Chapters provide up-to-date descriptions and comparative analyses of major migration regions in the North and South. The role of population movements in the formation of ethnic minority groups is examined, as is the impact of growing ethnic diversity on economies, cultures, and political institutions. Useful pedagogical features include accessible boxed examples, tables, maps, and suggestions for further reading. The companion website features an online-only chapter, additional case studies, links to relevant resources, and periodic updates. New to This Edition: Thoroughly revised with the latest information, analysis, theoretical developments, and policies. Addresses the impact of the global economic crisis since 2008. Covers the effects of climate change on migration and security. Discusses new types of labor migration; marriage migration; new areas of origin, transit, and destination; and other current trends. The leading text in the field, this authoritative work offers a global perspective on the nature of migration flows, why they occur, and their consequences for both origin and destination societies. Chapters provide up-to-date descriptions and comparative analyses of major migration regions in the North and South. The role of population movements in the formation of ethnic minority groups is examined, as is the impact of growing ethnic diversity on economies, cultures, and political institutions. Useful pedagogical features include accessible boxed examples, tables, maps, and suggestions for further reading. The companion website features an online-only chapter, additional case studies, links to relevant resources, and periodic updates"--Provided by publisher.